THE APPLICATION OF COOPERATIVE LEARNING MODEL IN PEDAGOGIC COURSE - Nuryani, Pupun (EDUTECH, 2015)
Abstract. Today the challenges of employment is more toward teamwork. Given the growing importance of cooperative interactions in employment, this should be anticipated by the education world, one of which through classroom instruction strategies. This study aimed to describe the initial condition of the characteristic of PGSD students’ ability inPedagogic course, to depic the application of cooperative learning in Pedagogic course, and to know the strengths and weaknesses of cooperative learning in Pedagogic course. This used qualitative approach with descriptive analysis method. The results showed that the initial condition of the characteristic of PGSD students’ ability in in Pedagogic coursebasically has a good enough quality. It was also found that. theapplication of cooperative learning is more preferable for students than lecturing method. The results conclude that the application of cooperative learning in Pedagogic course can improve the ability of students in the learning process.Keywords : Cooperative Learning Model, Pedagogic course,Abstrak. Dewasa ini tantangan lapangan pekerjaan lebih banyak berorientasi pada kerjasama tim. Mengingat semakin pentingnya interaksi kooperatif dalam lapangan pekerjaan, maka hal ini harus diantisipasi oleh dunia pendidikan salah satunya melalui strategi pembelajaran kelas. Penelitian ini bertujuan untuk mendeskripsikan kondisi awal karakteristik kemampuan mahasiswa PGSD pada mata kuliah pedagogik; mendeskripsikan penerapan model pembelajaran kooperatif pada mata kuliah pedagogik; mengetahui kelebihan dan kelemahan model pembelajaran kooperatif pada mata kuliah pedagogic. Penelitian ini menggunakan metode deskriptif analisis. Sedangkan pendekatan yang digunakan pada penelitian ini adalah pendekatan kualitatif.. Hasil penelitian menunjukan kondisi awal karakteristik kemampuan mahasiswa PGSD pada mata kuliah pedagogik pada dasarnya memiliki kualitas yang cukup baik. Hasil penelitian juga menunjukkan bahwa penerapan model pembelajaran kooperatif dalam mata kuliah pedagogik lebih disukai mahasiswa dibandingkan dengan menggunakan metode ceramah. Simpulan hasil penelitian, penerapan model pembelajaran kooperatif pada mata kuliah pedagogik dapat meningkatkan kemampuan mahasiswa dalam proses pembelajaran.Kata Kunci : model pembelajaran kooperatif, mata kuliah Pedagogik